Randomized controlled trials on acupuncture for migraine: research problems and coping strategies - Chen, Heqing (Ann Transl Med, 2019)
BACKGROUND: Acupuncture clinical trials have achieved certain results in verifying the efficacy and safety of acupuncture in recent years. However, there are still some shortcomings in trial design, data processing that obstructed the objective evaluation. METHODS: This article tried to summarize the common problems in randomized controlled trials evaluating acupuncture treatment for migraine. We searched seven databases from inception to Oct 19(th), 2017 and carried out a systematic review. According to this meta-analysis, we collected and synthesized the common problems and then summarized the main shortcomings. DISCUSSION: From aspects of trial design, statistical analysis and article writing, this paper illustrated the problems with examples, discussed the probable causes and accordingly put forward some recommendations to standardize the trial design, data processing and article reporting.